Identification and Preferences of Spa Industry in Bali - Oka Suryawardani, I Gusti Ayu; Wiranatha, Agung Suryawan; PETR, Christine; Purbanto, I Gusti Raka; Yudiastina, I Gusti Bagus Arya (E-Journal of Tourism, 2023)
Wellness tourism allows a person to maintain their personal wellbeing, maintaining health and quality of life. People are more conscious of their wellness during the trip. Spa industry which is part of the wellness tourism are growing rapidly in Bali. The research aimed: i) to analyze characteristics of spa treatment in Bali and preferences of spa treatment by customers, ii) to identify products and services provided by traditional and Thalasso Spa in Bali.  Research was conducted in Kuta, Seminyak, Canggu, Nusa Dua and Ubud as the center of spa treatment in Bali. Data was collected on January to April 2023 through interviewing 38 spa industries by using interview guides. Likert Scale was used to analyze the data in 1–5 scale.  Data was analyzed by using qualitative approach.  The results show that traditional spa treatments in Bali provide variety of products such as scrub, cream and lotion from herbs and natural ingredients from agriculture. Type of services available are traditional massage, aromatherapy, Thai massage, reflexology, hot stone massage and hot oil massage. Meanwhile, Thalasso is a therapy that is carried out using ingredients derived from the sea such as sea water, algae, seaweed, sand and sea mud and offers a wide range of spa treatments using technological spa equipment with excellent services. This therapy has only been found at the Grand Mirage Bali Resort since 1985 featuring an aqua medic pool with heated seaweed and sea water supported by 16 uniquely designed treatment rooms. The results also show that traditional massage is preferred by customers. Price competitiveness is one of the reasons why people choose traditional spa.  Sense of traditional massage has also been preferred by customers. Keywords: traditional massage, aromatherapy, oil massage, hot stone massage, Bali.